Komunikasi Antarbudaya Antara Masyarakat Pribumi Dengan Masyarakat Transmigrasi Di Desa Kedataran Kecamatan Maje Kabupaten Kaur - Pardela, Peko Andri; Yanto, Yanto; Octaviani, Vety (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Cultural diversity gave birth to many different cultures in Bengkulu Province, one of which is in Kedataran Village, Maje District, Kaur Regency. In the communication process between people of different cultures, a more comprehensive understanding is needed so that it does not become a conflict. This underlies the research conducted in Kedataran Village, with the aim of describing the intercultural communication process that occurs between indigenous people and transmigration communities in this area. This type of research is field research with a qualitative approach. Data collection techniques were interviews with key and main informants, as well as observation and documentation. This research uses the theory of intercultural communication (Ting-Toomey, 1985) which includes symbolic exchange, proces, different cultural communities, interactive situation, negotiate shared meanings, and societal embedded system. Based on the results of research and data analysis, it is concluded that 1) the use of intercultural communication symbols in Kedataran Village is the language used, namely Kaur, Javanese, and Indonesian, 2) although there are cultural differences but people are able to understand each other so that the communication process is quite harmonious, 3) different cultural communities between people coexist by applying mutual tolerance and mutual respect for differences, 4) interactive situations of intercultural communication during weddings, official village forums, and social activities, 5) negotiation of meaning is related to the substance of the issues conveyed such as conflicts due to differences in viewpoints and assessments of other cultures, 6) systems embedded in society shape the process as well as the results of intercultural encounters between indigenous and transmigration communities.